Design of high-speed, low-power, and area-efficient FIR filters - Liacha, Ahmed; Oudjida, Abdelkrim K; Ferguene, Farid; Bakiri, Mohammed; Berrandjia, Mohamed L (IET circuits, devices & systems, 2018)
In a recent work, we have introduced a new multiple constant multiplication (MCM) algorithm, denoted as RADIX-2r. The latter exhibits the best results in speed and power, comparatively with the most prominent algorithms. In this paper, the area aspect of RADIX-2r is more specially investigated. RADIX-2r is confronted to area efficient algorithms, notably to the cumulative benefit heuristic (Hcub) known for its lowest adder-cost. A number of benchmark FIR filters of growing complexity served for comparison. The results showed that RADIX-2r is better than Hcub in area, especially for high order filters where the saving ranges from 1.50% up to 3.46%. This advantage is analytically proved and experimentally confirmed using a 65nm CMOS technology. Area efficiency is achieved along with important savings in speed and power, ranging from 6.37% up to 38.01% and from 9.30% up to 25.85%, respectively. When MCM blocks are implemented alone, the savings are higher: 10.18%, 47.24%, and 41.27% in area, speed, and power, respectively. Most importantly, we prove that MCM heuristics using similar addition pattern (A-operation with the same shift spans) as Hcub yield excessive bit-adder overhead in MCM problems of high complexity. As such, they are not competitive to RADIX-2r in high order filters.